SOLIDARY CARE: A SOCIAL COMORITMENT FOR NURSING IN INTENSIVE CARE UNITS - Luiz Antônio Bettinelli; Alacoque Lorenzini Erdmann (Universidade Federal do Paraná, 1998)
In this study the authors proposed a new way of doing nursing, sustained by a conceptual framework (concepts of atmosphere of relationships, human being, health-disease, nursing, solidarity and solidary care). Such framework was experienced in the exercise of the solidary care in an intensive care unit (UTI). The found results showed the solidary care is composed by cognitive, affective, social, moral, physiologica and organizational values, positive and negative attitudes of the nursing personal and the influence of the atmosphere of UTI on the persons. The solidarity is a process of gradual construction done through sharing of knowledge and of feelings.lt could lead to a more authentic and true approach between the professionals and the patients, bringing larger satisfaction and valorization of life.